2018
DOI: 10.1021/acs.jafc.8b03312
|View full text |Cite
|
Sign up to set email alerts
|

Antiobesity Effect of Tricin, a Methylated Cereal Flavone, in High-Fat-Diet-Induced Obese Mice

Abstract: The antiobesity potential of tricin, a methylated cereal flavonoid, was examined using a high-fat-diet-induced obese mice model. The body weight ( P < 0.01) and body fat mass ( P < 0.05) were significantly decreased in the high-dose tricin supplementation group (TH: 200 mg/kg diet) in comparison to the high fat diet control group (CON) after a 12-week feeding trial. The serum (60.9 ± 2.09 mg/dL) and hepatic triglyceride levels (45.3 ± 4.42 nmol/mg protein) in the TH group were significantly decreased in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 43 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Chlorogenic acid was previously shown to inhibit adipocyte differentiation via AMPK activation [39,40]. Tricin suppressed the expression of transcription factors associated with adipocyte differentiation (PPARγ and C/EBPα) in obese mice fed a high-fat diet [41]. Collectively, the results suggest that these compounds are responsible for the anti-adipogenic activity of BS21.…”
Section: Discussionmentioning
confidence: 72%
“…Chlorogenic acid was previously shown to inhibit adipocyte differentiation via AMPK activation [39,40]. Tricin suppressed the expression of transcription factors associated with adipocyte differentiation (PPARγ and C/EBPα) in obese mice fed a high-fat diet [41]. Collectively, the results suggest that these compounds are responsible for the anti-adipogenic activity of BS21.…”
Section: Discussionmentioning
confidence: 72%
“…Traditional medicinal plants have huge natural compound resources and better safety in drug development and application. At present, several studies revealed the effective natural compounds of antiobesity are extracted from botany, including sulforaphene [12], daidzein [13], quercetin [14], hesperidin and capsaicin [15], methylated cereal flavonoid [16], and dietary phenolic [17], indicating the natural products are a great choice as potential candidates for treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Tricin is a flavonoid-type compound that has diverse properties, including antioxidant, anti-obesity, antidiabetic, anticancer, anti-influenza virus, anti-human cytomegalovirus, anti-inflammatory, antiangiogenic, antifungal, anti-adipogenic, insecticidal, and allelopathic activities [ 14 , 18 , 19 , 20 ]. However, it has not been reported to have inhibitory activity on XO.…”
Section: Resultsmentioning
confidence: 99%